Flamboyant : Un art de vivre dans les années trente. - Salamé, Louma; Boghossian, Jean; Dubois, Cécile (Bruxelles : Fondation Boghossian - Villa Empain, 2019)
Strebelle, Rodolphe ; Spilliaert, Léon ; Van de Woestijne, Gustave ; Carte, Anto ; Picabia, Francis ; Miró, Joan ; Jespers, Oscar ; van Dongen, Kees ; De Koninck, Louis Herman ; van de Velde, Henry ; Mallet-Stevens, Robert ; Chareau, Pierre ; Baugniet, Marcel-Louis ; Seuphor, Michel ; Kandinsky, Wassily ; Donas, Marthe ; De Smet, Gustave ; Tytgat, Edgard ; Matisse, Henri ; Ingrand, Max ; Akarova ; Magritte, René ; Colin, Paul ; Marfurt, Léo ; de Roeck, Lucien ; De Vlamynck, Geo ; Servranckx, Victor ; Tutundjian, Léon
Flamboyant. Un art de vivre dans les années trente, Fondation Boghossian - Villa Empain, Brussel, 28 maart - 6 oktober 2019
boek